Crustose coralline algae can contribute more than corals to coral reef carbonate production - Christopher E. Cornwall; Jérémy Carlot; Oscar Branson; Travis A. Courtney; Ben P. Harvey; Chris T. Perry; Andreas J. Andersson; Guillermo Diaz-Pulido; Maggie D. Johnson; Emma Kennedy; Erik C. Krieger; Jennie Mallela; et al. (Communications Earth & Environment, 2023)
Crustose coralline algae can contribute equal or even larger amounts of calcium carbonate to coral reefs than corals, yet their contribution is often underrepresented or omitted in coral reef carbonate budgets, according to a conceptual model developed from a meta-analysis of calcification rates and a case study in French Polynesia.